Governing the boundary: between socio-environmental vulnerability and state capacity in Temajuk Village, Indonesia - Alfath Bagus Panuntun El Nur Indonesia; Defila Priana Falarima; Said Khaidir; Ari Surida; Nur Muliasari MS; Tara Charissa Oktavia S (Department of Government Studies Universitas Muhammadiyah Makassar, 2024)
This research explored the challenges and solutions to governing Indonesian border areas, with a particular focused on Temajuk Village in Sambas Regency, West Kalimantan Province. The research highlighted two critical issues: increased smuggling of illegal goods and socio-environmental vulnerabilities, particularly regarding the conservation of endangered sea turtles. The research identified systemic weaknesses, including inadequate state capacity, limited law enforcement and socio-economic disparity factors that exacerbate transnational challenges. The findings exposed potential national threats caused by geographic isolation, and porous borders that facilitate illicit activities, such as drug and alcoholic drinks smuggling, with serious social consequences, including youth delinquency, early marriage, declining education levels, and increased health risks, such as the spread of HIV/AIDS. Furthermore, unsustainable exploitation of sea turtles for cultural and economic purposes also threatens biodiversity. This article proposes a multifaceted strategy to address these interrelated issues, prioritizing effective border management, sustainable economic development, and strong community engagement. Strengthening institutional and individual capacities at the village level, improving law enforcement and encouraging cross-sectoral cooperation between village, district, provincial and national governments are essential. Highlighting the threats to Temajuk Village, this research promotes evidence-based local strategies that align national security with ecological and social well-being and offers insights into sustainable governance in border areas.